2014
DOI: 10.1097/hjh.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine plus candesartan combination increases blood pressure control regardless of race and improves the side effect profile

Abstract: Objectives:DISTINCT (reDefining Intervention with Studies Testing Innovative Nifedipine GITS – Candesartan Therapy) aimed to determine the dose–response and tolerability of nifedipine GITS and/or candesartan cilexetil therapy in participants with hypertension.Methods:In this 8-week, multinational, multicentre, randomized, double-blind, placebo-controlled study, adults with mean seated DBP of at least 95 to less than 110 mmHg received combination or monotherapy with nifedipine GITS (N) 20, 30 or 60 mg and cande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 43 publications
1
27
1
Order By: Relevance
“…Response surface modeling showed that nifedipine GITS/candesartan combinations provided greater SBP and DBP lowering after 8 weeks of treatment compared with respective component monotherapies or placebo in all SBP and DBP subgroups, consistent with the main study results24 (Figure 1). For example, mean ± SE reductions in SBP in the N60C32, N60, C32, and placebo treatment groups were 29.8 ± 2.5, 23.0 ± 2.7, 20.3 ± 2.8, and 8.0 ± 2.7 mm Hg, respectively, in the SBP ≥160 mm Hg subgroup and were 20.0 ± 2.1, 13.1 ± 2.0, 14.3 ± 1.9, and 35 ± 1.9 mm Hg, respectively, in the SBP <160 mm Hg subgroup.…”
Section: Resultssupporting
confidence: 83%
“…Response surface modeling showed that nifedipine GITS/candesartan combinations provided greater SBP and DBP lowering after 8 weeks of treatment compared with respective component monotherapies or placebo in all SBP and DBP subgroups, consistent with the main study results24 (Figure 1). For example, mean ± SE reductions in SBP in the N60C32, N60, C32, and placebo treatment groups were 29.8 ± 2.5, 23.0 ± 2.7, 20.3 ± 2.8, and 8.0 ± 2.7 mm Hg, respectively, in the SBP ≥160 mm Hg subgroup and were 20.0 ± 2.1, 13.1 ± 2.0, 14.3 ± 1.9, and 35 ± 1.9 mm Hg, respectively, in the SBP <160 mm Hg subgroup.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, there is no debate about the effectiveness of the combination strategy, but the question is more whether it should always be preceded by monotherapy, or whether combination therapy may be the initial approach . RCTs tend to confirm that initial two‐drug combination strategies achieve earlier BP control when compared with strategies that add a second drug after monotherapy . Similar evidence has accumulated in observational studies to some extent .…”
Section: Introductionmentioning
confidence: 98%
“…Pharmacokinetic analyses demonstrated that steady‐state concentrations of nifedipine and candesartan were reached by week 28. Although there was a tendency for candesartan concentrations to be higher in Black than other groups, there was no difference in the efficacy of the FDC for BP reduction between racial subgroups, as noted also in the DISTINCT main study (although efficacy analyses in DISTINCT did not take into account addition of a third drug) …”
Section: Discussionmentioning
confidence: 74%
“…This multinational, multicentre, open‐label study evaluated, for the first time, the long‐term safety and efficacy of FDC N/C once daily in a large population ( n = 508) with moderate‐to‐severe essential hypertension. The target dose of N60/C32 was selected based on outcomes from the DISTINCT study, and the majority of patients attained this dose following titration (87·2% at weeks 44–52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation